Early mathematical competencies and later achievement: Insights from the Longitudinal Study of Australian Children. - Carmichael, Colin; MacDonald, A; MacDonald, Amy (My University, 2017)
International research suggests that early mathematical competence predicts later mathematical achievement. In this article, we explore the relationship between mathematical competencies at 4–5 years, as measured by teacher ratings, and later results on Years 3, 5, 7 and 9 National Assessment Program – Literacy and Numeracy (NAPLAN) numeracy tests. Data from a nationally representative sample of 2343 children participating in the Longitudinal Study of Australian Children (LSAC) are examined. In line with international studies, we report moderate correlations between preschool-entry mathematics and later NAPLAN numeracy test results. However, analysis of individual growth trajectories indicates that early mathematics predicts the initial (Year 3) level, but not subsequent growth. This suggests that early mathematical competencies are important for enhancing achievement in early schooling, but that the quality of mathematics education provided in the schooling years is critical for future development.
Keywords: Childhood and child development; Childhood and child development